Pengaruh Profitabilitas dan Struktur Aktiva terhadap Struktur Modal (Studi Kasus pada Perusahaan Sub Sektor Transportasi Di Bursa Efek Asia Tenggara Periode 2012-2018) - Deni Sunaryo (INOBIS: Jurnal Inovasi Bisnis dan Manajemen Indonesia, 2020)
The discussion leads to the influence of Profitability and Asset Structure on Capital Structure which shows the inequality of the results in previous studies. Therefore, this study aims to determine the effect of profitability and asset structure on capital structure. This study uses an empirical study for the transportation sub-sector companies in Southeast Asia in 2012-2018. The data used in this study are secondary data from transportation companies listed on the stock exchange during 2012-2018. The sampling method was taken and resulted in 8 companies as samples. The statistical analysis used in this research is multiple regression method, partial test and simultaneous test with SPSS version 23. The results of the study partially conclude that profitability has a significant negative effect on capital structure and asset structure has a significant negative effect on capital structure. The results of the research simultaneously show that the calculated F value is greater than the F table value, namely 6.348 > 3.17, and the significance value is smaller than 0.05 (0.003 < 0.05). Thus, Profitability and Asset Structure simultaneously influence Capital Structure. The study concluded that all independent variables have an influence on capital structure. Based on the test results of the coefficient of determination, the value of adjust R Square is 19.3%, the remaining 80.7% is influenced by other variables outside of this study.